Modified ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

By combining carbon and sodium ion conductors on the surface and grain boundary of the positive electrode material of sodium ferric pyrophosphate, a three-dimensional conductive network is formed, which solves the problems of low conductivity and poor diffusion, significantly improves the charge transfer rate and structural stability of the material, and improves the rate performance.

CN119650674AActive Publication Date: 2025-03-18CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202510167930.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-03-18
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

The electron conductivity of sodium ferric pyrophosphate positive electrode material is low and the sodium ion diffusivity is poor, resulting in large polarization of the charge and discharge process and relatively poor rate performance, which cannot meet the needs of fast charge and discharge.

Method used

By uniformly combining carbon and sodium ion conductors on the surface and grain boundaries of sodium ferric pyrophosphate positive electrode material, a three-dimensional conductive network is formed, the charge transfer rate is improved, and the precursor is prepared by spray drying to control the uniform morphology and structural stability of the material.

Benefits of technology

The charge transfer rate of the positive electrode material is significantly improved, the structural stability of the material is enhanced, the cycle performance and rate performance are improved, so that it can meet the needs of fast charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650674A_ABST
    Figure CN119650674A_ABST
Patent Text Reader

Abstract

The invention provides a modified ferric sodium phosphate pyrophosphate positive electrode material and a preparation method and application thereof, the modified ferric sodium phosphate pyrophosphate positive electrode material comprises a ferric sodium phosphate pyrophosphate positive electrode material and a carbon and sodium ion conductor, the carbon and sodium ion conductor is enriched on the surface and grain boundary of the ferric sodium phosphate pyrophosphate positive electrode material in a uniform composite phase, and the sodium ion conductor is NaxMOy. A composite phase material formed by carbon and a sodium ion conductor is used for coating primary particles and secondary particles of the positive electrode material, a three-dimensional conductive / conductive ion network is formed on the grain boundary and the surface of the material, and the charge and ion transmission rate of the material is high; and the three-dimensional coating layer can protect the material from being eroded by electrolyte, the structure stability is good, and the cycle performance and the rate performance of the material are excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically relates to a mixed conductor modified sodium iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] With the development of power storage, electric vehicles, and portable electronic devices, limited lithium resources cannot meet the rapidly expanding market demand for lithium-ion batteries. Sodium is abundant in reserves and relatively low in cost. It has similar physical and chemical properties and electrode potentials to lithium, and the electrochemical reaction mechanism of sodium-ion batteries is similar to that of lithium-ion batteries. All these have promoted the market competition between sodium-ion batteries and lithium-ion batteries. Sodium-ion batteries are expected to become a substitute for lithium-ion batteries in the field of large-scale energy storage.

[0003] The positive electrode material determines the performance of the battery to a large extent. At present, the positive electrode materials of sodium ion batteries mainly include layered oxides, Prussian blue and polyanions. Among them, the polyanion type sodium iron phosphate pyrophosphate positive electrode material has attracted extensive attention and research due to its low cost, good structural stability, excellent cycle performance and high discharge voltage. However, sodium iron phosphate pyrophosphate has low electronic conductivity and poor sodium ion diffusion, resulting in large polarization in the charge and discharge process and relatively poor rate performance, which cannot meet the needs of fast charge and discharge.

[0004] Carbon coating and bulk doping can improve the electronic conductivity of sodium iron pyrophosphate positive electrode materials and the diffusion rate of sodium ions in the crystal, thereby improving the performance of the material to a certain extent. However, the modification effect is not obvious and cannot solve the problem of low sodium ion transmission rate at the grain boundaries of primary particles of the material. Summary of the invention

[0005] In response to the above technical problems, the present application provides a modified sodium iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof.

[0006] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a modified sodium iron phosphate pyrophosphate positive electrode material is provided, comprising a sodium iron phosphate pyrophosphate positive electrode material, carbon and a sodium ion conductor, wherein the carbon and the sodium ion conductor are uniformly composited and enriched on the surface and grain boundaries of the sodium iron phosphate pyrophosphate positive electrode material, and the sodium ion conductor is Na x MO y , wherein M is one or more of Zr, Al, Cr, Bi, Te, Pb, Co, Sb, Se, Nb, Ta, W and Mo, the value of x is 1~2, and the value of y is 2~4.

[0007] Furthermore, the secondary particles of the modified sodium iron phosphate pyrophosphate positive electrode material are solid spherical structures with a tap density of 1.1-2.1 g / cm3 , particle size D50 is 2~10μm.

[0008] Furthermore, the mass ratio of the sodium iron pyrophosphate, carbon and sodium ion conductor is 84-98:1-8:1-8.

[0009] In a second aspect, a method for preparing a modified sodium iron phosphate pyrophosphate positive electrode material is provided, comprising: Mixing a phosphorus source, a ferrous source, a sodium source, a nano M source and a dispersant in deionized water to obtain a dispersion; spray drying the dispersion to obtain a precursor; The precursor is heat treated in an inert atmosphere or a reducing atmosphere to obtain Na x MO y and carbon composite coated sodium iron phosphate pyrophosphate positive electrode material, wherein M is one or more of Zr, Al, Cr, Bi, Te, Pb, Co, Sb, Se, Nb, Ta, W and Mo, the value of x is 1-2, and the value of y is 2-4.

[0010] In a third aspect, a sodium ion battery is provided, comprising the aforementioned modified sodium iron phosphate pyrophosphate positive electrode material or the modified sodium iron phosphate pyrophosphate positive electrode material prepared by the aforementioned preparation method.

[0011] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The mixed conductor modified sodium iron phosphate pyrophosphate positive electrode material provided by the present invention uses a composite formed by conductive carbon and sodium ion conductor to coat primary particles and secondary particles of the positive electrode material, forming a three-dimensional conductive network at the grain boundary and surface of the positive electrode material, so that the charge transfer rate of the positive electrode material is high; and the three-dimensional coating layer can protect the material from being corroded by the electrolyte, has good structural stability, and has excellent material cycle performance and rate performance.

[0012] The present invention adopts a spray drying method to prepare a precursor, which can control the uniform morphology of the electrode material. Nano-scale M source oxide and dispersant are dispersed in the spray liquid. Under the action of the dispersant, the nano M source will be evenly distributed at the grain boundaries of the precursor primary particles after spray drying. After calcination, the dispersant is carbonized, and the M source reacts with the surface material and the sodium source of the precursor during the calcination process, and grows epitaxially on the surface of the material to obtain a sodium ion conductor, constructing a three-dimensional electron / ion transmission network from the grain boundary of the material to the surface, and significantly improving the charge transfer rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0014] Figure 1 This is the XRD diagram of the sodium iron pyrophosphate positive electrode material prepared in Example 1.

[0015] Figure 2 TEM and element mapping images of the sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1; (a) is a HAADF-STEM image, (b), (c), (d), and (e) are element mapping images of O, Fe, C, and Sb, respectively, (f) and (g) are TEM images, and (h) is a HRTEM image.

[0016] Figure 3 This is the SEM image of the sodium iron pyrophosphate positive electrode material prepared in Example 1.

[0017] Figure 4 This is a charge and discharge curve diagram of the sodium iron pyrophosphate positive electrode material prepared in Example 1 at different rates.

[0018] Figure 5 This is a charge and discharge curve diagram of the sodium iron pyrophosphate positive electrode material prepared in Comparative Example 1 at different rates.

[0019] Figure 6 This is the XRD diagram of the sodium iron pyrophosphate positive electrode material prepared in Example 2. DETAILED DESCRIPTION

[0020] The present invention provides a mixed conductor modified sodium iron phosphate pyrophosphate positive electrode material, comprising a sodium iron phosphate pyrophosphate positive electrode material, carbon and a sodium ion conductor, wherein the carbon and the sodium ion conductor are uniformly composited and enriched on the surface and grain boundaries of the sodium iron phosphate pyrophosphate positive electrode material (i.e., the carbon and the sodium ion conductor are uniformly composited and coated on the secondary particles and primary particles of the sodium iron phosphate pyrophosphate positive electrode material), and the sodium ion conductor is Na x MO y , wherein M is one or more of Zr, Al, Cr, Bi, Te, Pb, Co, Sb, Se, Nb, Ta, W and Mo, the value of x is 1 to 2, for example, 1, 2, and the value of y is 2 to 4, for example, 2, 3, 4.

[0021] In some preferred embodiments, the secondary particles are solid spherical structures with a tap density of 1.1-2.1 g / cm 3, D50 is 2~10μm, for example, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc.

[0022] In some preferred embodiments, the mass ratio of sodium ferric pyrophosphate, carbon, and sodium ion conductor is 84-98:1-8:1-8, for example, 98:1:1, 97:1:2, 97:2:1, 96:1:3, 96:3:1, 96:2:2, 95:4:1, 95:1:4, 95:3:2, 95:2:3, 94:5:1, 94:1:5, 94:4:2, 94:2:4, 94:3:3, 93:6:1, 93:1:6, 93:5:2, 93:2:5, 93:4:3, 93:3:4, 92:6:2, 92:2:6, 92:5:3, 92:3:5, 92:4:4, 91:7:2, 91:7:3, 91:8:4, 91:9:1 1:3:6, 91:5:4, 91:4:5, 90:8:2, 90:2:8, 90:7:3, 90:3:7, 90:6:4, 90:4:6, 90:5:5, 89:8:3, 89:3:8, 89:7:4, 89:4:7, 89:6:5, 89:5:6, 88:8:4, 88:4:8, 8 8:7:5, 88:5:7, 88:6:6, 88:8:4, 88:4:8, 88:7:5, 88:5:7, 88:6:6, 87:8:5, 87:5:8, 87:7:6, 87:6:7, 86:8:6, 86:6:8, 86:7:7, 85:8:7, 85:7:8, 84:8:8, etc.

[0023] Some embodiments of the present invention provide a method for preparing a mixed conductor modified sodium iron phosphate pyrophosphate positive electrode material, comprising: Mixing a phosphorus source, a ferrous source, a sodium source, a nano M source, a dispersant and deionized water to obtain a dispersion; spray drying the dispersion to obtain a precursor; The precursor is heat treated in an inert atmosphere or a reducing atmosphere to obtain Na x MO y and carbon composite coated sodium iron phosphate pyrophosphate positive electrode material, wherein M is one or more of Zr, Al, Cr, Bi, Te, Pb, Co, Sb, Se, Nb, Ta, W and Mo, the value of x is 1 to 2, for example, 1, 2, and the value of y is 2 to 4, for example, 2, 3, 4.

[0024] In some preferred embodiments, the phosphorus source includes one or more of sodium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate.

[0025] In some preferred embodiments, the ferrous source includes one or more of ferrous acetate, ferrous nitrate, ferrous oxalate and ferrous sulfate.

[0026] In some preferred embodiments, the sodium source includes one or more of sodium dihydrogen phosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate and sodium citrate.

[0027] In some preferred embodiments, the dispersant includes one or more of polyvinyl pyrrolidone, polyacrylamide, and sodium carboxymethyl cellulose.

[0028] The inert atmosphere may be an inert gas atmosphere, such as an atmosphere produced by an inert gas such as argon or neon, or may be a nitrogen atmosphere.

[0029] In some preferred embodiments, the nano Mo source includes ZrO 2 、Al 2 O 3 CrO 3 、Bi 2 O 3 、TeO 2 , Pb 2 O 3 、Co 2 O 3 , Sb 2 O 3 , SeO 2 , Nb 2 O 5 、 2 O 5 , WO 3 and MoO 3 One or more of .

[0030] In some preferred embodiments, the particle size of the nano-M source is 5 to 50 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc.

[0031] In some preferred embodiments, the molar ratio of the nano M source to the ferrous source is 0.1~0.6:2.1~3, for example, 0.1:2.1, 0.1:2.3, 0.1:2.5, 0.1:2.8, 0.1:3, 0.2:2.1, 0.2:2.5, 0.2:2.8, 0.2:3, 0.3:2.1, 0.3:2.5, 0.3:2.8, 0.3:3, 0.4:2.1, 0.4:2.5, 0.4:2.8, 0.4:3, 0.5:2.1, 0.5:2.5, 0.5:2.8, 0.5:3, 0.6:2.1, 0.6:2.5, 0.6:2.8, 0.6:3, etc.

[0032] In some preferred embodiments, the amount of the dispersant is 1-10% of the total mass of the phosphorus source, ferrous source, sodium source, carbon source and nano M source, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.

[0033] In some preferred embodiments, the sodium source, phosphorus source and ferrous source are prepared according to a molar ratio of Na to P and Fe of 3-4:4:2-3.

[0034] In some preferred embodiments, the heat treatment includes pre-firing and calcination; the pre-firing temperature is 250-350°C, for example, 250°C, 280°C, 300°C, 320°C, 350°C, etc.; the pre-firing time is 2-10h, for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc.; the calcination temperature is 450-650°C, for example, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C, 600°C, 620°C, 650°C, etc.; the calcination time is 3-15h, for example, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc.

[0035] In some preferred embodiments, the inlet air temperature of the spray drying is 120-240° C., the outlet air temperature is 90-120° C., and the spray feed flow rate is 50-2000 mL / h.

[0036] Some embodiments of the present invention provide a sodium ion battery, comprising the aforementioned mixed conductor modified sodium iron phosphate pyrophosphate positive electrode material or the mixed conductor modified sodium iron phosphate pyrophosphate positive electrode material prepared by the aforementioned preparation method.

[0037] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0038] Example 1 (1) Mix sodium dihydrogen phosphate, ferrous acetate, Sb in a mass ratio of 4.79:5.21:0.29. 2 O 3 The raw materials were mixed with 6% deionized water of the total weight of the raw materials, and 4% polyvinyl pyrrolidone of the total weight of the raw materials was added, and stirred evenly. The mixed solution was stirred at room temperature for 2 h to ensure that the raw materials were fully dissolved and dispersed to obtain a dispersion.

[0039] (2) The dispersion was dried by a spray dryer with the inlet air temperature set to 180°C, the outlet air temperature set to 105°C, and the spray feed flow rate set to 1000 mL / h to obtain a precursor powder.

[0040] (3) Sintering the precursor powder in a high-purity nitrogen atmosphere, heating the temperature to 350°C at a rate of 2°C / min, keeping the temperature for 4 hours, then heating the temperature to 550°C, keeping the temperature for 10 hours, and then naturally cooling to obtain the positive electrode material.

[0041] The XRD pattern of the obtained positive electrode material is shown in Figure 1 As shown, from Figure 1 It can be seen that the XRD diagram shows that the obtained product is pure phase sodium iron phosphate pyrophosphate; the TEM and element mapping diagrams of the obtained positive electrode material are as follows Figure 2 As shown in the TEM image, it can be seen that the coating is coated on the surface of the primary particles (i.e., enriched at the grain boundaries). Combined with the element mapping, it can be seen that C and Sb are evenly distributed in the coating. And through high-resolution TEM analysis of the coating, it is found that Sb in the coating is NaSbO 3 present at the grain boundaries, which indicates that C and NaSbO 3 The composite material is evenly distributed on the grain boundary of the sodium iron phosphate pyrophosphate material, and the coating is dense. 3 At the same time, it is also coated on the secondary particle surface of sodium iron pyrophosphate material in a composite state, namely C and NaSbO 3 It is enriched in a composite state on the surface and grain boundaries of the sodium iron pyrophosphate positive electrode material, that is, C and NaSbO 3 (NaSbO 3 The sodium ion conductor is evenly distributed in the coating layer, and the two are densely composited and evenly coated on the surface and grain boundaries of the sodium iron pyrophosphate positive electrode material. Therefore, the chemical formula of the product can be determined to be Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C&NaSbO 3 , carbon and NaSbO 3 The composite material is uniformly coated on the primary and secondary particles of the sodium iron pyrophosphate cathode material in a dense composite state. 3 As a sodium ion conductor; and based on the density of the coating layer, it can be inferred that the positive electrode material having the dense coating layer has an excellent effect of inhibiting the corrosion of the electrolyte on the material.

[0042] The SEM image of the obtained positive electrode material is shown in Figure 3 As shown, from Figure 3 It can be seen that the cathode material is a secondary particle composed of primary particles, and the secondary particles are solid spherical structures. After testing, the tap density of the obtained cathode material is 1.4g / cm³ and the particle size D50 is 4.2μm.

[0043] The sodium ferric phosphate pyrophosphate positive electrode material prepared above is used to assemble a sodium ion battery. Other components of the battery include a sodium metal negative electrode, an electrolyte, and a separator. The specific process of positive electrode sheet preparation and battery assembly is as follows: the sodium ferric phosphate pyrophosphate positive electrode material is fully ground and mixed with a conductive agent (SuperP) and a binder (PVDF) in NMP at a mass ratio of 8:1:1, and then coated on the surface of an aluminum foil. After drying in a vacuum drying oven, it is made into a disc with a diameter of 12 mm to obtain a positive electrode sheet. The prepared positive electrode sheet, sodium sheet negative electrode, glass fiber separator, electrolyte (1 mol L -1 NaClO 4 The 2025 button cells were assembled in a glove box filled with argon and with water and oxygen concentrations less than 0.01 ppm.

[0044] The assembled sodium-ion batteries were subjected to charge and discharge tests to evaluate their capacity, cycle stability and rate performance.

[0045] The charge and discharge curves of the battery assembled with the positive electrode material obtained in Example 1 at different rates are shown in the figure below: Figure 4 As shown in the figure, it can be seen that the battery assembled with the obtained positive electrode material has excellent discharge specific capacity and rate performance.

[0046] Comparative Example 1 (1) Mix the raw materials of sodium dihydrogen phosphate and ferrous acetate in a mass ratio of 4.79:5.21 with deionized water accounting for 6% of the total mass of the raw materials, add polyvinyl pyrrolidone, a dispersant accounting for 4% of the total mass of the raw materials, and stir evenly. Stir the mixture at room temperature for 2 hours to ensure that the raw materials are fully dissolved and dispersed to obtain a dispersion.

[0047] (2) The dispersion was dried by a spray dryer with the inlet air temperature set to 180°C, the outlet air temperature set to 105°C, and the spray feed flow rate set to 1000 mL / h to obtain a precursor powder.

[0048] (3) Sintering the precursor powder in a high-purity nitrogen atmosphere, heating the temperature to 350°C at a rate of 2°C / min, keeping the temperature for 4 hours, then heating the temperature to 550°C, keeping the temperature for 10 hours, and then naturally cooling to obtain the positive electrode material.

[0049] The positive electrode material obtained in Comparative Example 1 was assembled into a battery using the same battery assembly method as in Example 1. The charge and discharge curves of the battery at different rates are shown in FIG. Figure 5By comparing the battery assembled with the positive electrode material obtained in Example 1 and Comparative Example 1, it is found that the discharge specific capacity of the battery assembled with the positive electrode material obtained in Example 1 at different rates is significantly higher than that of the battery assembled with Comparative Example 1, and the rate performance of the battery assembled with Example 1 is also significantly improved compared with that of the battery assembled with Comparative Example 1. After analysis, this is due to the difference between C and NaSbO in Example 1. 3 It is in a composite state and evenly coated on the surface and grain boundaries of the positive electrode material, thereby improving the ion and electron transport properties of the positive electrode material.

[0050] Comparative Example 2 (1) Mix the raw materials of sodium dihydrogen phosphate and ferrous acetate in a mass ratio of 4.79:5.21 with deionized water accounting for 6% of the total mass of the raw materials, add polyvinyl pyrrolidone, a dispersant accounting for 4% of the total mass of the raw materials, and stir evenly. Stir the mixture at room temperature for 2 hours to ensure that the raw materials are fully dissolved and dispersed to obtain a dispersion.

[0051] (2) The dispersion was dried by a spray dryer with the inlet air temperature set to 180°C, the outlet air temperature set to 105°C, and the spray feed flow rate set to 1000 mL / h to obtain a precursor powder.

[0052] (3) Mix the precursor powder with Sb 2 O 3 The mixture was ball-milled and sintered in a high-purity nitrogen atmosphere. The temperature was increased to 350°C at a rate of 2°C / min, and the mixture was kept warm for 4 hours. The temperature was then increased to 550°C and the mixture was kept warm for 10 hours. The mixture was then naturally cooled to obtain a composite modified sodium iron phosphate pyrophosphate positive electrode material.

[0053] Example 2 The mass ratio of diammonium phosphate, ferric nitrate nonahydrate, sodium bicarbonate, Al 2 O 3 The raw materials are mixed with 5% deionized water of the total weight of the raw materials, and 7% polyacrylamide as a dispersant of the total weight of the raw materials is added and stirred evenly. The mixed solution is stirred at room temperature for 3 hours to ensure that the raw materials are fully dissolved and dispersed to obtain a dispersion.

[0054] The dispersion was dried by a spray dryer, with the inlet air temperature set to 220° C., the outlet air temperature set to 115° C., and the spray feed flow rate set to 1500 mL / h to obtain a precursor powder.

[0055] The precursor powder was sintered in a high-purity nitrogen atmosphere, heated to 300°C at a heating rate of 3°C / min, kept at this temperature for 6 hours, then heated to 600°C, kept at this temperature for 12 hours, and then naturally cooled to obtain the sodium iron phosphate pyrophosphate positive electrode material. The XRD pattern of the obtained product is shown in Figure 6 As shown, from Figure 6It can be seen that the XRD diagram shows that the obtained product is pure phase sodium iron phosphate pyrophosphate. Combining the raw materials, raw material properties and the product obtained in Example 1, the chemical formula of the obtained product is Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C&NaAlO 2 , C and NaAlO 2 The dense composite state is coated on the surface of the primary particles, NaAlO 2 As a sodium ion conductor.

[0056] The cathode material is a secondary particle composed of primary particles, which is a solid spherical structure. The tap density of the secondary particles is 1.5g / cm³ and D50 is 5.1μm.

[0057] Example 3 The mass ratio of ammonium dihydrogen phosphate, ferrous oxalate, sodium acetate, Nb 2 O 5 The raw materials are mixed with 7% deionized water of the total weight of the raw materials, and 5% dispersant sodium carboxymethyl cellulose of the total weight of the raw materials are added and stirred evenly. The mixed solution is stirred at room temperature for 2.5 hours to ensure that the raw materials are fully dissolved and dispersed to obtain a dispersion.

[0058] The dispersion was dried by a spray dryer, with the inlet air temperature set to 200° C., the outlet air temperature set to 110° C., and the spray feed flow rate set to 1200 mL / h to obtain a precursor powder.

[0059] The precursor powder was sintered in a high-purity nitrogen atmosphere, heated to 320°C at a heating rate of 2.5°C / min, kept warm for 5 hours, then heated to 580°C, kept warm for 13 hours, and then naturally cooled to obtain a sodium iron pyrophosphate positive electrode material. Based on the raw materials, raw material properties and the product obtained in Example 1, the chemical formula of the obtained product is Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C&NaNbO 3 , C and NaNbO 3 The dense composite state is coated on the surface of the primary particles, NaNbO 3 As a sodium ion conductor.

[0060] The cathode material is a secondary particle composed of primary particles, which is a solid spherical structure. The tap density of the secondary particles is 1.6g / cm³ and D50 is 6.6μm.

[0061] Example 4 Sodium dihydrogen phosphate, ferric nitrate nonahydrate, and MoO 3 The raw materials were mixed with 5.5% deionized water, and 4.5% polyacrylamide was added as a dispersant, and stirred evenly. The mixture was stirred at room temperature for 2 hours to ensure that the raw materials were fully dissolved and dispersed to obtain a dispersion.

[0062] The dispersion was dried by a spray dryer, with the inlet air temperature set to 210° C., the outlet air temperature set to 118° C., and the spray feed flow rate set to 1800 mL / h to obtain a precursor powder.

[0063] The precursor powder was sintered in a high-purity nitrogen atmosphere, heated to 340°C at a heating rate of 2°C / min, kept warm for 8 hours, then heated to 650°C, kept warm for 9 hours, and then naturally cooled to obtain a sodium iron pyrophosphate positive electrode material. Based on the raw materials, raw material properties and the product obtained in Example 1, the chemical formula of the obtained product is Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C&Na 2 MoO 4 , C and Na 2 MoO 4 The dense composite state is coated on the surface of the primary particles, Na 2 MoO 4 As a sodium ion conductor.

[0064] The cathode material is a secondary particle composed of primary particles, which is a solid spherical structure. The tap density of the secondary particles is 1.3g / cm³ and D50 is 3.8μm.

[0065] The positive electrode materials obtained in Examples 2-4, Comparative Examples 1 and 2 were assembled into batteries using the same battery assembly method as in Example 1, and the batteries assembled in Examples 1-4 and Comparative Examples 1-2 were subjected to cycle performance tests at 0.5C. The results are shown in Table 1.

[0066] As can be seen from Table 1, the batteries assembled in each embodiment have a higher discharge specific capacity and better cycle performance. Compared with the battery assembled in Comparative Example 1, the battery assembled in Example 1 not only has a significantly improved specific capacity, but also has a significantly improved cycle performance. After analysis, this may be because the single carbon coating in Comparative Example 1 generally has pores, while the composite coating in Example 1 is denser and has a better effect in inhibiting the corrosion of the electrolyte on the material.

[0067] Compared with the battery assembled in comparative example 2, the battery assembled in example 1 not only has significantly improved specific capacity, but also has significantly improved cycle performance, which indicates that the coating method of example 1 has a better modification effect.

[0068] Table 1 Cyclic data of batteries assembled in various embodiments and comparative examples at 0.5 C The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Modified sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The invention comprises a sodium iron phosphate pyrophosphate positive electrode material, carbon and a sodium ion conductor, wherein the carbon and the sodium ion conductor are uniformly composited and enriched on the surface and grain boundaries of the sodium iron phosphate pyrophosphate positive electrode material, and the sodium ion conductor is Na x MO y , wherein M is one or more of Zr, Al, Cr, Bi, Te, Pb, Co, Sb, Se, Nb, Ta, W and Mo, the value of x is 1~2, and the value of y is 2~4.

2. The modified sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that: The secondary particles of the modified sodium iron phosphate pyrophosphate positive electrode material are solid spherical structures with a tap density of 1.1-2.1 g / cm 3 , particle size D50 is 2~10μm.

3. The modified sodium iron phosphate pyrophosphate positive electrode material according to claim 1 or 2, characterized in that: The mass ratio of sodium iron pyrophosphate, carbon and sodium ion conductor is 84-98:1-8:1-8.

4. A method for preparing a modified sodium iron phosphate pyrophosphate positive electrode material, characterized in that: include: Mixing a phosphorus source, a ferrous source, a sodium source, a nano M source, a dispersant and deionized water to obtain a dispersion; spray drying the dispersion to obtain a precursor; The precursor is heat treated in an inert atmosphere or a reducing atmosphere to obtain Na x MO y and carbon composite coated sodium iron phosphate pyrophosphate positive electrode material, wherein M is one or more of Zr, Al, Cr, Bi, Te, Pb, Co, Sb, Se, Nb, Ta, W and Mo, the value of x is 1-2, and the value of y is 2-4.

5. The method for preparing the modified sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: The phosphorus source includes one or more of sodium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate; The ferrous source includes one or more of ferrous acetate, ferrous nitrate, ferrous oxalate and ferrous sulfate; The sodium source includes one or more of sodium dihydrogen phosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate and sodium citrate; The dispersant includes one or more of polyvinyl pyrrolidone, polyacrylamide, and sodium carboxymethyl cellulose.

6. The method for preparing the modified sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: The nano M source includes at least one of ZrO2, Al2O3, CrO3, Bi2O3, TeO2, Pb2O3, Co2O3, Sb2O3, SeO2, Nb2O5, Ta2O5, WO3 and MoO3; The particle size of the nano-M source is 5 to 50 nm.

7. The method for preparing the modified sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: The molar ratio of the nano M source to the ferrous source is 0.1-0.6:2.1-3; The amount of the dispersant is 1-10% of the total mass of the phosphorus source, ferrous source, sodium source, carbon source and nano M source; The sodium source, phosphorus source and ferrous source are prepared according to the molar ratio of Na to P and Fe of 3-4:4:2-3.

8. The method for preparing the modified sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: The heat treatment includes pre-firing and calcining; The pre-burning temperature is 250-350°C; the pre-burning time is 2-10h; The calcination temperature is 450-650° C. and the calcination time is 3-15 hours.

9. The method for preparing the modified sodium iron phosphate pyrophosphate positive electrode material according to claim 4, characterized in that: The inlet air temperature of the spray drying is 120-240°C, the outlet air temperature is 90-120°C, and the spray feed flow rate is 50-2000 mL / h.

10. A sodium ion battery, characterized in that It comprises the modified sodium iron phosphate pyrophosphate positive electrode material as described in any one of claims 1 to 3 or the modified sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method as described in any one of claims 4 to 9.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN117059786A

  • Sodium-ion battery layered positive electrode material coated with polyanion positive electrode material and preparation method of sodium-ion battery layered positive electrode material

    CN117199301A

  • Preparation method and application of ferric sodium pyrophosphate positive electrode material

    CN117819512A

  • Preparation method of pyrophosphoric acid polyanionic sodium ion battery positive electrode material

    CN117878287A

  • Sodium ferric pyrophosphate sodium ion battery positive electrode material and preparation method thereof

    CN118047362A

Cited By

  • Se anion doped ferric sodium pyrophosphate / carbon positive electrode active material and preparation method and application thereof

    CN120709323A

  • Sodium ion positive electrode material, preparation method thereof and battery

    CN120895618A

  • High-entropy ferric pyrophosphate sodium ion battery positive electrode material and preparation method thereof

    CN121862743A

  • A modified sodium iron phosphate pyrophosphate positive electrode material, a preparation method thereof, a positive electrode sheet, a secondary battery and an electric device

    CN122739330A